The Effectiveness of Indigenous Conflict Management Strategies in Localized Contexts. (February 2022) - Lundy, Brandon D.; Collette, Tyler L.; Downs, J. Taylor
The professionalization of addressing conflict creates a field filled with specialists highly trained to apply modularized and manualized, often evidence-based solutions. But how effective are these professionalized conflict management strategies in Indigenous and localized cultural contexts compared to homegrown Indigenous approaches? While instances of these Indigenous peacebuilding and conflict management strategies are routine throughout the world, to date, no one has attempted to test which conflict management approaches are most effective empirically, nor has the literature sufficiently addressed the contexts in which strategies are most helpful. Using multi-dimensional scaling and chi-square tests of independence applied to a similarity matrix of co-occurrences from select Outline of Cultural Materials subjects from the Human Relations Area Files cultural database, this study tests the hypothesis: Indigenous conflict management strategies are more effective (i.e., less associated conflict) than non-Indigenous conflict management strategies in Indigenous contexts. We show that Indigenous conflict management approaches co-occur with conflict less often than non-Indigenous strategies. From an applied perspective, when we break conflict into four discreet types—sociocultural/interpersonal, political, legal/judicial, and economic—Indigenous conflict management strategies co-occur most often with socio-cultural types of conflicts. The results suggest that Indigenous approaches are more effective in Indigenous contexts overall, while they are most often applied to socio-cultural and interpersonal conflicts. Based on our findings, homegrown solutions effectively manage, resolve, and transform localized conflicts.